Rancang Bangun Antena Semi Circular Dengan Teknik GDS (Defect Ground Structure) untuk Meningkatkan Bandwidth Antena Pada Aplikasi WIFI - Trushero Kharisma Claudiani; koesmarijanto koesmarijanto; hendro darmono (Jurnal Jaringan Telekomunikasi, 2021)
The increasing need for the amount of data sent and the speed of data transmission via wireless technology has resulted in high interest in devices with wide bandwidth. Improving antenna design is one way to increase Bandwidth. The antenna is designed in such a way as to get the antenna parameters that are effective, one of which is to increase the antenna bandwidth. The techniques used to improve microstrip antenna parameters is the Defect Ground Structure (DGS) technique. The methods used are calculation, simulation and measurement. The results of the semicircular array microstrip antenna without DGS, the return loss parameter value is -13.7 dB and the VSWR value is 1.518 and has a gain of 1.3 dBi at a frequency of 2455 MHz. This antenna has the form of a bidirectional radiation pattern. The antenna bandwidth obtained is 14 MHz. The result of the semicircular array microstrip antenna with DGS, the return loss parameter value is -14.4 dB and the VSWR value is 1.469 and has a gain of 2.8 dBi at a frequency of 2455 MHz. This antenna has the form of a directional radiation pattern. The antenna bandwidth obtained is 10 MHz. The conclusion of this research is that the semicircular array microstrip antenna without DGS has a smaller bandwidth than the semicircular array microstrip antenna with DGS, which is a difference of 3.5 MHz.